Larval rearing of turbot (Scophthalmus maximus): Effect of density of living food - Fernández-Pato, Carlos; Martínez-Tapia, Concha; Chereguini-Fernández-Maquieira; María del Olvido (2012)
Growth and survival of turbot larvae rearing using high density of living food are described in this paper. Comparisons between some groups of larvae fed on high density of prey with those that received a lower amount of food did not show significative differences (p>0.5)in t-Student test applied to growth, but on the contrary tests of Breslow and Mantel-Cox showed significative differences on survival p=0.0000. No